North Korea’s Fourth Nuclear Test - Süvari, Kahraman (Overcoming Controversies in East Asia, 2017)
North Korean state media announced on January 6, 2016 that North Korea had successfully conducted its fourth underground nuclear test. Most importantly, it was also claimed by the North that it was a hydrogen bomb test. It is already known that North Korea previously performed three underground nuclear tests in 2006, 2009, and 2013. Despite all the pressure from the international community, why did North Korea conduct the fourth nuclear test? The main aim of this study is to examine North Korea’s 2016 nuclear test. The study consists of three parts. Firstly, the four nuclear tests performed by the North since 2006 will be analyzed. Although it is highly controversial that North Korea’s fourth nuclear test was a hydrogen bomb test, as a matter of fact it was a test of a nuclear explosive device. But, how was the last nuclear test different from previous tests? In the second section, the possible reasons behind the fourth nuclear test will be discussed. Different factors might drive the North to perform the nuclear testing. However, in this study, it is argued that North Korea’s leadership carried out the fourth nuclear test mainly because it wants to strengthen its nuclear deterrent against the perceived threats to itself. Lastly, the study will end with a general assessment about the main findings.